Answer:
hello : 6.23x10^14 > 8.912x10^12^12
Step-by-step explanation:
let : A= 6.23x10^14 and B = 8.912x10^12
A= (6.23x10^2) x10^12 ... because : 10^14 = 10^2x10^12
A = 623 x 10^12
623 > 8.912
so : A > B
First we solve what we can solve.
<span>y</span>-3= 2/3<span>(</span>x-1)
We first multiply
<span>y</span>-3= 2/3 (x) - 2/3
Then we move the -3 and it becomes +3 on the other side
y= 2/3 (x) - 2/3 + 3
And we solve what we can to get our answer.
y= 2/3 (x) + 2 1/3
Since it is mid-way you would multiply it by 2 so, 8x2=16
Your answer is 16.
Hope I helped <3